(untitled) (Cuea Journal of Business and Economics, 2025)
The objective of the study was to examine the effect of market capitalization on financial performance of cross-listed companies listed at the Nairobi Securities Exchange. An event study methodology was used. The research focused on the all the 7 NSE firms that have been cross-listed. The study proposed to use secondary data which was collected from the NSE. Since the current study utilized quantitative data only, positivism was adopted. The research used an event study methodology. The researcher collected quantitative data using a secondary data collection sheet. Before being entered into the E-views (v-10) software program for analysis, the data was filtered and screened for accuracy, missing values, and outliers. Market capitalization had a negligible impact on financial performance of NSE firms before cross listing (β=0.003, p=0.030). The research deduced that market capitalization had a favourable and noteworthy effect on the financial performance of the NSE cross-listed companies. Consequently, strengthening market capitalization positively impacts the financial performance of cross-listed companies listed at the NSE. A higher market capitalization can also indicate a company's strong financial standing, while lower market capitalization might suggest a listed company's financial health is not as strong.